New constraints on the Cretaceous geodynamics of paleo-Pacific plate subduction: Insights from the Xiaojiang–Beizhang granitoids, Zhejiang Province, southeast China - Liu, L.; Hu, R.; Zhong, H.; Tang, Y.; Yang, J.; Li, Zhen; Zhao, J.; Shen, N. (Elsevier BV, 2018)
The relationship between the evolution of Cretaceous magmatism along the southeastern margin of Eurasia and subduction of the paleo-Pacific plate remains controversial. Here we investigate the petrogenesis of the Xiaojiang–Beizhang ferroan and magnesian granitoids, melanocratic microgranular enclaves (MME) that are found within the granitoids, and an associated mafic dyke exposed in southeast China to provide new constraints on the geodynamics of paleo-Pacific plate subduction. Zircon U–Pb ages indicate that the ferroan and magnesian granitoids were emplaced in the Cretaceous (ca. 120 and 110 Ma, respectively), and that the MME and mafic dyke are coeval with their host granitoids. Geochemical characteristics imply that the granitoids were produced by partial melting of crustal rocks and mixed with mantle-derived magmas. The MME are derivatives of the mafic magmas that intruded the silicic magmas. Two phases of mafic magmatism are evident. Stage 1 mafic rocks (the ca. 120 Ma MME) were derived mainly from the subcontinental lithospheric mantle (SCLM) with some contribution from asthenospheric mantle. The parental mafic magmas for Stage 2 (the ca. 110 Ma MME and mafic dykes) were derived from interaction and metasomatism of the SCLM and asthenosphere with slab-derived fluids. Iron enrichment or depletion in the granitoids was controlled mainly by oxygen fugacity and pressure. Our new data, combined with previously published data from Cretaceous igneous rocks in southeastern China, reveal major geochemical changes at 136 and 118 Ma, respectively. The 132–119 Ma igneous rocks record the minimal addition of slab-derived components to their source, and provide strong evidence for an abrupt change in the direction of motion of the paleo-Pacific plate from southwest to northwest at ca. 125–122 Ma.